A ferrocene redox-active triazolium macrocycle that binds and senses chloride - White, Nicholas G.; Beer, Paul D. (Beilstein Journal of Organic Chemistry, 2012)
A ferrocene bis(triazole) macrocycle was synthesised in good yield by the Eglinton coupling of an acyclic bis(alkyne) precursor and characterised in the solid state by X-ray crystallography. Alkylation gives the corresponding triazolium macrocycle, which binds chloride and benzoate strongly in CD3CN solution through favourable charge-assisted C–H···anion interactions, as evidenced by 1H NMR titration experiments. Preliminary electrochemical studies reveal that the redox-active macrocycle is capable of sensing chloride in CH3CN solution.
Keywords: anion binding; C–H···anion interactions; electrochemistry; ferrocene; triazolium